Analisis Pengelolaan Digital Community dalam Mendukung Penjualan di Showroom Ralif Motor - Rahmi, Halimatur; Rina, Rina; Adha, Fajar; Saputra, Muhammad Fitri; Anisa, Nor (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
This journal examines the management of a digital community at Ralif Motor Showroom to support marketing efforts and business performance in addressing competitive challenges. The digital community is utilized to strengthen customer interactions, promotion, and loyalty, contributing to market expansion and building consumer trust. The study employs a qualitative approach through in-depth interviews with showroom representatives and several customers. The analysis reveals that while the digital community has positive impacts, such as increasing showroom visibility and fostering closer relationships with customers, its implementation faces challenges. Key issues include limited resources, inefficient manual recording processes, and suboptimal social media strategies. As a solution, this study recommends adopting an integrated management system, such as technology for stock management and transaction recording. Additionally, implementing a more structured and innovative social media strategy is necessary to support promotions and enhance customer interactions effectively. By taking these steps, the showroom is expected to improve operational efficiency, expand market share, and drive sustainable business growth.